KAJIAN MAKNA RAGAM HIAS RUMAH ADAT BANTAYO PO’ BOIDE KABUPATEN GORONTALO - Almer Hassan Ali (LPPM Institut Desain dan Bisnis Bali, 2021)
This research generally aims to gain knowledge about the traditional values of the Bantayo Po 'Boide Traditional House by trying to express the cultural values of the people of Gorontalo Regency. This research Specifically a variety of decorative meanings in the Bantayo Po' Boide traditional house. This research uses descriptive method by collecting various qualitative and quantitative data relating to the form and symbolic meaning of the Bantayo Po' Boide Traditional House of Gorontalo Regency, while the data collection uses the method of Observation, Documentation, Interview and Literature Study. The results of this study, the writer found a variety of decorative meanings in the Bantayo Po' Boide traditional house. 1) The front of the house there is a stylized ornament of lotus and breadfruit plants and grouse. 2) Ornaments on the edge of the banyan and triangular tree ceiling. 3) Ornaments in the ventilation of doors and windows are stylized in the form of spears and shields. 4) The living room ceiling ornament is a combination of lotus flowers and chains. 5) Ornaments on lyst plank are stylized from jasmine plants.